A cross-sectional study of essential surgical, obstetric, and anaesthesia care capacity in the public sector in Fiji. - Ashneel Sundar; Jope Makutu; Ifereimi Waqainabete; Grace Zhang; Jemesa Tudravu; Josese Turagava; Kiki Maoate; Rajeev Patel; Rennie Xinrui Qin (PLOS Global Public Health)
The Lancet Commission on Global Surgery indicator collection highlighted gaps in surgical, obstetric, and anaesthesia (SOA) care in Fiji. Our study is the first comprehensive assessment of essential SOA care capacity in Fiji to guide national surgical planning. In February 2021, we conducted a cross-sectional survey of public hospitals in Fiji using the World Health Organization-Program in Global Surgery and Social Change surgical assessment tool. We surveyed 18 facilities, including three divisional hospitals (DHs) and 15 subdivisional hospitals (SDHs). Twenty-two functional operating rooms (ORs) and 27 post-anaesthesia care beds served 884,887 people. Surgical care was concentrated in DHs and only delivered in select SDHs during outreaches. While SDHs had OR space, they lacked equipment, supplies, and human resources. From 2016 to 2021, surgical volume per 100,000 population increased by approximately 50% from 1,490 to 2,248; however, SOA specialists density per 100,000 population increased marginally from 5.8 to 7.1. There is significant variation across divisions. The Northern division has more ORs (4.55), SOA specialists (9.1), and surgical volume (3,731) per 100,000 population than the Central (2.40, 7.9, 2,367) and Western (1.78, 5.3, 1,519) divisions. This is due to more OR space and functioning, specialist post creation, and outreach services to SDHs. Policy recommendations include upgrading key SDHs with essential SOA care capacity, growing the SOA workforce, strengthening facility maintenance and climate resilience, and strengthening outreach programs. Investment in surgical care capacity must be urgently increased to meet the population's needs.